2014
DOI: 10.4236/ijg.2014.510097
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Overview of Bioresponse to Magnetic Fields on the Earth’s Surface

Abstract: This survey points to the mechanisms of bioresponse caused by magnetic fields (MFs), paying attention to their action not only on ions, molecules and macromolecules, but also on cells, tissues and organisms. The significance of findings concerning the MF-dependence of cell proliferation, necrosis or apoptosis was judged by comparing the results obtained in a solenoid, where an MF can be added to the geomagnetic field (GMF), with those obtained in a magnetically shielded room, where the MFs can be attenuated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In particular, the static magnetic field of significant induction ( ) inhibits the DNA synthesis in mice, therefore, suppressing the tumor growth and even affecting the normal tissues, for example, decreasing the amount of blood cells 2 . On the other hand, the inhibition of apoptosis by the magnetic field can cause an increase in the risk of cancer development 3 , 4 . However, the latter effect is often considered to be related to the reactive oxygen species production rather than DNA synthesis 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the static magnetic field of significant induction ( ) inhibits the DNA synthesis in mice, therefore, suppressing the tumor growth and even affecting the normal tissues, for example, decreasing the amount of blood cells 2 . On the other hand, the inhibition of apoptosis by the magnetic field can cause an increase in the risk of cancer development 3 , 4 . However, the latter effect is often considered to be related to the reactive oxygen species production rather than DNA synthesis 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 On the other hand, a static magnetic field can inhibit apoptosis, increasing the risk of cancer. 3,4 Besides that, a lowfrequency electromagnetic field can promote DNA fragmentation in human cells, 5 while a relatively weak static magnetic field of 0.2 T significantly affects the DNA synthesis rate. 6 These observations determine the fundamental importance of the interaction of the magnetic field with soft matter.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a static magnetic field of significant induction (9.4 T) inhibits DNA synthesis in mice, therefore, suppressing tumor growth 2 . On the other hand, a static magnetic field can inhibit apoptosis, increasing the risk of cancer 3,4 . Besides that, a low‐frequency electromagnetic field can promote DNA fragmentation in human cells, 5 while a relatively weak static magnetic field of 0.2 T significantly affects the DNA synthesis rate 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that a magnetic field could inhibit apoptosis and therefore increase the risk of cancer. 3,4 Besides that, extremely low-frequency electromagnetic field can cause DNA fragmentation in human cells. 5 Besides that, the relatively weak static magnetic field of 0.2 T significantly affects the rate of the DNA synthesis rate.…”
Section: Introductionmentioning
confidence: 99%